¿Es posible celebrar contratos de créditos hipotecarios digitales en el Perú? - Raygada Castillo, Miguel Ángel (2022)
There is the technology and the demand for the conclusion of digital mortgage loans in Peru; however, there are some legal and institutional limitations that prevent its granting entirely online, such as: excessive protection of the debtor in the Peruvian regulation, the lack of a secondary originator of mortgages, the lack of regulation for the execution of digital public deeds, and the need for precision in the Securities Law and in the Civil Procedure Code.